Housing Regulations for Low-Income People in Indonesia - Erni HERAWATI; Suparjo SUPARJO; Ratih LESTARINI (International Journal of Environmental, Sustainability, and Social Science, 2023)
Indonesia had 11 million home backlogs in 2020 and 93% of this number are low-income and poor people. South Tangerang is one of the cities in Indonesia where 80% of the area is built by private developers, and 50% of which is developed by three major companies. The existence of large-scale housing they’ve built has caused local people to move to the peripheral of the housing or to places on the outskirts of the city. This paper analysis how the regulations give companies the authority to control large land area and how its impact to low-income people. By using the socio-legal method, this study aims to reveal the implication of law in society. The results showed that the existence of large-scale housing did not contribute to fulfilling the housing needs of low-income people in South Tangerang City. Regulations in the housing sector have not had any implications for the fulfilment of housing needs for low-income people. There are no small houses that the local people can afford.